1992
DOI: 10.1111/j.1365-2125.1992.tb04130.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of glyceryl trinitrate on alpha‐adrenoceptor mediated contraction in the human internal mammary artery.

Abstract: 1. Sympathomimetic amines have been considered to be related to vasospasm. Previous studies showed that the human internal mammary artery (IMA) was capable of weak beta‐adrenoceptor mediated relaxation and that alpha‐adrenoceptor agonists may induce contraction in the human IMA. 2. We investigated the effects of glyceryl trinitrate (GTN), a vasodilator agent often used perioperatively, on alpha‐adrenoceptor mediated contraction in the human IMA. 3. Discarded human IMA segments were taken from 37 patients who u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

1994
1994
1996
1996

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…On the other hand, the present study demonstrates that the ET-1-induced contraction is not fully reversed by GTN in the human IMA indicated by the fact that the maximal relaxation was 76.44%. In contrast, GTN has been demonstrated to reverse completely the contraction induced by U46619 [7] or a-adrenoceptor agonists [20]. This observation is partially in accordance with others [30].…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…On the other hand, the present study demonstrates that the ET-1-induced contraction is not fully reversed by GTN in the human IMA indicated by the fact that the maximal relaxation was 76.44%. In contrast, GTN has been demonstrated to reverse completely the contraction induced by U46619 [7] or a-adrenoceptor agonists [20]. This observation is partially in accordance with others [30].…”
Section: Discussionsupporting
confidence: 71%
“…In the previous studies [7,20], we have observed that although GTN is a potent vasodilator in reversing contraction induced by a number of vasoconstrictors such as the thromboxane A2 mimetic U46619 [7] and a-adrenoceptor agonists [20], it is less effective in the human IMA if applied to prevent the contraction induced by these constrictors although the mechanism is unclear. In this study, we continuously observed this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Any discarded distal IMA segments were collected and placed in a container with oxygenated, physiological solution (Krebs') maintained at 4"C, and then transferred to the laboratory. The details of collecting, dissecting, and mounting of the IMA rings and the organ bath technique have been described previously [14][15][16][17][18][19]. Briefly, the rings were stretched-up in progressive steps to determine the length-tension curve for each ring.…”
Section: Methodsmentioning
confidence: 99%